Inhibition of NF-κB Pathway and Modulation of MAPK Signaling Pathways in Glioblastoma and Implications for Lovastatin and Tumor Necrosis Factor-Related Apoptosis Inducing Ligand (TRAIL) Combination Therapy. - Pi Chu Liu; Gang Lu; Yi Deng; Cheng Dong Wang; Xian Wei Su; Jing Ye Zhou; Tat Ming Chan; Xiang Hu; Wai Sang Poon (PLoS ONE, 2017)
Glioblastoma is a common malignant brain tumor and it is refractory to therapy because it usually contains a mixture of cell types. The tumor necrosis factor-related apoptosis inducing ligand (TRAIL) has been shown to induce apoptosis in a range of tumor cell types. Previously, we found that two human glioblastoma cell lines are resistant to TRAIL, while lovastatin sensitizes these glioblastoma cells to TRAIL-induced cell death. In this study, we investigated the mechanisms underlying the TRAIL-induced apoptosis in human glioblastoma cell lines by lovastatin. Furthermore, we have confirmed the anti-tumor effect of combination therapy with lovastatin and TRAIL in the subcutaneous brain tumor model. We showed that lovastatin significantly up-regulated the expression of death receptor 5 (DR5) in glioblastoma cell lines as well as in tumor-bearing mice with peri-tumoral administration of lovastatin. Further study in glioblastoma cell lines suggested that lovastatin treatment could inhibit NF-κB and Erk/MAPK pathways but activates JNK pathway. These results suggest that lovastatin sensitizes TRAIL-induced apoptosis by up-regulation of DR5 level via NF-κB inactivation, but also directly induces apoptosis by dysregulation of MAPK pathway. Our in vivo study showed that local peri-tumoral co-injection of lovastatin and TRAIL substantially reduced tumor growth compared with single injection of lovastatin or TRAIL in subcutaneous nude mice model. This study suggests that combined treatment of lovastatin and TRAIL is a promising therapeutic strategy to TRAIL-resistant glioblastoma.